2017
DOI: 10.18632/oncotarget.19068
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic heterogeneity and prostate cancer mortality in Hispanic/Latino men: a population-based study

Abstract: BackgroundFew studies focus on prostate cancer (PCa) outcomes in Hispanic/Latino men. Our study explores whether Hispanic/Latino subgroups demonstrate significantly different prostate cancer-specific mortality (PCSM) relative to Non-Hispanic White (NHW) and Non-Hispanic Black (NHB) men.MethodsWe extracted a population-based cohort of men diagnosed with local-regional PCa from 2000-2013 (n= 486,865). PCSM was measured in racial/ethnic groups: NHW (n=352,886), NHB (n= 70,983), Hispanic/Latino (n= 40,462), and As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Although disparities in outcomes among black men with advanced prostate cancer are well established, to the best of our knowledge less is known regarding Hispanic men with this lethal disease. Chinea et al examined a large cohort of men with prostate cancer and observed that, even among Hispanic men, substantial ethnic heterogeneity exists and may influence prostate cancer–specific mortality . Unfortunately, in cancer registry data, >40% of Hispanic/Latino patients have unspecified Hispanic origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although disparities in outcomes among black men with advanced prostate cancer are well established, to the best of our knowledge less is known regarding Hispanic men with this lethal disease. Chinea et al examined a large cohort of men with prostate cancer and observed that, even among Hispanic men, substantial ethnic heterogeneity exists and may influence prostate cancer–specific mortality . Unfortunately, in cancer registry data, >40% of Hispanic/Latino patients have unspecified Hispanic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Chinea et al examined a large cohort of men with prostate cancer and observed that, even among Hispanic men, substantial ethnic heterogeneity exists and may influence prostate cancer-specific mortality. 30 Unfortunately, in cancer registry data, >40% of Hispanic/Latino patients have unspecified Hispanic origin. Therefore, future research will need to examine disaggregated race/ethnicity data to determine whether differences in ADT strategy exist among different subgroups (eg, Mexican American, Puerto Rican) and whether cultural factors contribute to observed disparities.…”
Section: Discussionmentioning
confidence: 99%
“…We selected model parameters that were broadly based on known or putative prostate cancer risk factors as well as the following clinical and demographic information in the data set: age, 7 body mass index (BMI), 8 diabetes status, 9 smoking status, 10 emphysema, asthma, race 11 (white, black, Native American, Asian, or multiracial), ethnicity 12 (Hispanic or other), hypertension, 13 heart disease, 14 vigorous exercise habits, 15 and history of stroke. 16 We included these parameters in the ANN for two main reasons: For the purposes of potential future clinical integration, these parameters are routinely captured in the EMR, and in contrast to traditional statistical models, ANNs can do a better job at deciphering nonlinear relationships and making strong inferences with interdependent variables.…”
Section: Data Sets and Parameter Selectionmentioning
confidence: 99%
“…The available national data on the epidemiology of cancer among diverse racial/ethnic groups are commonly reported by broad racial/ethnic categories such as “Hispanic.” Few studies have investigated differences by Hispanic subgroup ( 16 , 30 ). Existing studies have considered rates in specific states such as Florida ( 16 , 31 ), but do not include all Hispanic subgroups ( 29 , 32 ), or focus on only one specific cancer type ( 33 ).…”
Section: Introductionmentioning
confidence: 99%